PENENTUAN HARGA JUAL KAMAR MELALUI IMPLEMENTASI ACTIVITY BASED COSTING SYSTEM PADA PT TASIK RIA RESORT MANADO - Tumanduk, Thalia Claudia; Ilat, Ventje; Gamaliel, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Development services company primarily in the field of tourism and hospitality, led to increasing competition among hotels. Because it takes strategy to excel in competing, by minimizing and calculate the cost of production effectively so that the selling price is low. The lower the selling price of the product into a high sales rate. Method of activity based costing (ABC) is very effective in determining the slling price, because ABC is a method of charging is to charge and collect a fee based activities based on the behavior of existing activities. This study aims to: (1) obtain the calculation result by using ABC method in determining the selling price of room at PT Tasik Ria Resort Manado (2) to compare the selling price of room at PT Tasik Ria Resort Manado using traditional accounting method and ABC. The method of analysis used in this research is descriptive method of comparative and the type of research used is descriptive qualitative. The results obtained that there is a difference between the selling price of PT Tasik Ria Resort Manado and ABC selling price, where the calculation of ABC in the rom types Pool View, Sea View and Grand Sea View rooms gives a smaller result than the selling price set by the management. While in the room type Garden View ABC calculation is higher than the sale price of rooms that have been set by the hotel management.Keywords: Activity Based Costing, Activity, Selling Price of Room